Discrete-Time Steady-State Control of Interconnected Systems Based on Pseudoinversion Concept - Zhiteckii, L.S.; Solovchuk, K.Yu. (Кибернетика и вычислительная техника, 2017)
The purpose of the paper is to generalize the results obtained by the authors in their last works which are related to the asymptotic properties of the pseudoinverse model-based method for designing an efficient steady-state control of interconnected systems with uncertainties and arbitrary bounded disturbances and also to present some new results.